FRANCHISING AS AN EFFECTIVE FORM OF BUSINESS ORGANIZATION - Атаманчук, З.; Нестерчук, Н. (SWorldJournal, 2024)
Franchising activity in international business is a current theme of scientific research by both domestic and foreign scientists. This theme has been actively researched in recent years, then it becomes more and more important in the world economy. The ro